2011
DOI: 10.1002/poc.1731
|View full text |Cite
|
Sign up to set email alerts
|

Homoaromaticity in aza‐ and phosphasemibullvalenes. A computational study

Abstract: The enthalpies of activation ΔH‡ for the Cope rearrangement in several aza‐ and phosphasemibullvalenes have been investigated by MP4/cc‐pVDZ//MP2/cc‐pVDZ and CCSD(T)/cc‐pVDZ//MP2/cc‐pVDZ calculations. One tetraazasemibullvalene and several phosphasemibullvalenes were found to have vanishing ΔH‡ values, which together with calculated large negative Nucleus Independent Chemical Shift (NICS) values and geometrical data show that these molecules have delocalized and bishomoaromatic minima. Furthermore, three azase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
1

Year Published

2013
2013
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 43 publications
(65 reference statements)
1
26
1
Order By: Relevance
“…After removal of the solvent under vacuum, purification by column chromatography (silica gel, petroleum ether/diethyl ether/triethylamine = 100:3:1) gave product 2. Compound 2 a: Yellow oil; 55 % (84 mg); 1 21.68, 28.00, 28.95, 30.13, 32.80, 35.32, 35.66, 43.24, 59.42, 79.82, 81.76, 92.54, 178.95, 181.16 20.87, 21.04, 27.89, 28.62, 29.69, 32.28, 35.04, 35.53, 43.35, 79.89, 81.05, 86.44, 114.88, 120.83, 129.46, 157.99, 178.54, 182.47 21.53, 22.40, 27.81, 28.20, 30.48, 32.81, 35.28, 35.61, 43.16, 79.68, 80.07, 81.92, 128.55, 129.55, 129.84, 133.24, 164.77, 178.07, 182.47 21.21, 27.95, 28.70, 29.84, 32.35, 35.10, 35.64, 43.38, 55.65, 79.85, 81.03, 87.06, 114.58, 115.61, 152.17, 153.74, 178.82, 182.67 14.16, 23.28, 23.60, 26.24, 27.98, 28.07, 28.78, 29.17, 35.20, 35.67, 35.78, 46.04, 83.48, 85.32, 86.30, 115.38, 120.84, 129.47, 158.41, 177.92, 182.85 General procedure for nucleophilic ring opening of 2,6-diazasemibullvalene 1 a with thiol derivatives 2,6-Diazasemibullvalene 1 a (0.5 mmol, 136 mg) in CH 2 Cl 2 (2 mL) was treated with 1-propanethiol (1.5 mmol, 58 mL) and the reaction mixture was stirred at rt overnight. After removal of the solvent under vacuum, purification by column chromatography (silica gel, petroleum ether/diethyl ether/triethylamine = 100:2:1) gave 3 as a colorless oil (61 %, 106 mg); 1 21.31, 22.51, 23.22, 28.02, 29.78, 31.74, 31.82, 35.46, 35.67, 37.73, 43.35, 61.18, 79.57, 81.10, 180.96, 181.08 ppm; HRMS: m/z calcd for C 21 General procedure for nucleophilic ring-opening of 1 a with carboxylic acid derivatives 2,6-Diazasemibullvalene 1 a (0.5 mmol, 136 mg) in CH 2 Cl 2 (2 mL) was treated with carboxylic acid (1.5 mmol) and the reaction mixture was stirred at room temperature overnight.…”
Section: Experimental Section General Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…After removal of the solvent under vacuum, purification by column chromatography (silica gel, petroleum ether/diethyl ether/triethylamine = 100:3:1) gave product 2. Compound 2 a: Yellow oil; 55 % (84 mg); 1 21.68, 28.00, 28.95, 30.13, 32.80, 35.32, 35.66, 43.24, 59.42, 79.82, 81.76, 92.54, 178.95, 181.16 20.87, 21.04, 27.89, 28.62, 29.69, 32.28, 35.04, 35.53, 43.35, 79.89, 81.05, 86.44, 114.88, 120.83, 129.46, 157.99, 178.54, 182.47 21.53, 22.40, 27.81, 28.20, 30.48, 32.81, 35.28, 35.61, 43.16, 79.68, 80.07, 81.92, 128.55, 129.55, 129.84, 133.24, 164.77, 178.07, 182.47 21.21, 27.95, 28.70, 29.84, 32.35, 35.10, 35.64, 43.38, 55.65, 79.85, 81.03, 87.06, 114.58, 115.61, 152.17, 153.74, 178.82, 182.67 14.16, 23.28, 23.60, 26.24, 27.98, 28.07, 28.78, 29.17, 35.20, 35.67, 35.78, 46.04, 83.48, 85.32, 86.30, 115.38, 120.84, 129.47, 158.41, 177.92, 182.85 General procedure for nucleophilic ring opening of 2,6-diazasemibullvalene 1 a with thiol derivatives 2,6-Diazasemibullvalene 1 a (0.5 mmol, 136 mg) in CH 2 Cl 2 (2 mL) was treated with 1-propanethiol (1.5 mmol, 58 mL) and the reaction mixture was stirred at rt overnight. After removal of the solvent under vacuum, purification by column chromatography (silica gel, petroleum ether/diethyl ether/triethylamine = 100:2:1) gave 3 as a colorless oil (61 %, 106 mg); 1 21.31, 22.51, 23.22, 28.02, 29.78, 31.74, 31.82, 35.46, 35.67, 37.73, 43.35, 61.18, 79.57, 81.10, 180.96, 181.08 ppm; HRMS: m/z calcd for C 21 General procedure for nucleophilic ring-opening of 1 a with carboxylic acid derivatives 2,6-Diazasemibullvalene 1 a (0.5 mmol, 136 mg) in CH 2 Cl 2 (2 mL) was treated with carboxylic acid (1.5 mmol) and the reaction mixture was stirred at room temperature overnight.…”
Section: Experimental Section General Methodsmentioning
confidence: 99%
“…Compound 2 a: Yellow oil; 55 % (84 mg); 1 21.68, 28.00, 28.95, 30.13, 32.80, 35.32, 35.66, 43.24, 59.42, 79.82, 81.76, 92.54, 178.95, 181.16 20.87, 21.04, 27.89, 28.62, 29.69, 32.28, 35.04, 35.53, 43.35, 79.89, 81.05, 86.44, 114.88, 120.83, 129.46, 157.99, 178.54, 182.47 21.53, 22.40, 27.81, 28.20, 30.48, 32.81, 35.28, 35.61, 43.16, 79.68, 80.07, 81.92, 128.55, 129.55, 129.84, 133.24, 164.77, 178.07, 182.47 21.21, 27.95, 28.70, 29.84, 32.35, 35.10, 35.64, 43.38, 55.65, 79.85, 81.03, 87.06, 114.58, 115.61, 152.17, 153.74, 178.82, 182.67 14.16, 23.28, 23.60, 26.24, 27.98, 28.07, 28.78, 29.17, 35.20, 35.67, 35.78, 46.04, 83.48, 85.32, 86.30, 115.38, 120.84, 129.47, 158.41, 177.92, 182.85 General procedure for nucleophilic ring opening of 2,6-diazasemibullvalene 1 a with thiol derivatives 2,6-Diazasemibullvalene 1 a (0.5 mmol, 136 mg) in CH 2 Cl 2 (2 mL) was treated with 1-propanethiol (1.5 mmol, 58 mL) and the reaction mixture was stirred at rt overnight. After removal of the solvent under vacuum, purification by column chromatography (silica gel, petroleum ether/diethyl ether/triethylamine = 100:2:1) gave 3 as a colorless oil (61 %, 106 mg); 1 21.31, 22.51, 23.22, 28.02, 29.78, 31.74, 31.82, 35.46, 35.67, 37.73, 43.35, 61.18, 79.57, 81.10, 180.96, 181.08 ppm; HRMS: m/z calcd for C 21 General procedure for nucleophilic ring-opening of 1 a with carboxylic acid derivatives 2,6-Diazasemibullvalene 1 a (0.5 mmol, 136 mg) in CH 2 Cl 2 (2 mL) was treated with carboxylic acid (1.5 mmol) and the reaction mixture was stirred at room temperature overnight. After removal of the solvent under vacuum, purification by column chromatography (silica gel, petroleum ether/diethyl ether/triethylamine = 100:5: 20.55, 21.93, 22.93, 27.94, 28.38, 31.24, 33.31, 35.47, 35.67, 43.41, 80.02, 80.45, 82.08, 169.02, 177.15, 181.45 14.08, 21.08, 21.63, 22.47, 23.34, 23.37, 25.79, 26.13, 26.33, 26.60, 26.75, 26.82, 31.01, 32.90, 38.46, 38.82, 40.94, 41.18, 43.31, 79.57, 79.88, 82.01, 169.36, 177.19, 181.90 21.27, 22.26, 27.33, 27.78, 28.85, 32.52, 35.17, 35.41, 38.84, 43.21, 79.48, 79.94, 81.27, 176.63, 177.95, 182.00 ppm; HRMS: m/z calcd for C 23 21.53, 22.40, 27.81, 28.20, 30.48, 32.82, 35.28, 35.62, 43.16, 79.68, 80.01, 81.93, 128.55, 129.55, 129.85, 133.24, 164.77, 178.08, 182.47 21.75, 27.82, 28.22, 35.37, 35.66, 45.83, 55.47, 80.49, 80.65, 82.91, 113.82, 122.10, 131.82, 164.51, 163.63, 178.24, 182.91…”
Section: Experimental Section General Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…16 In a similar approach, the structures of aza-and phosphasemibullvalenes and barbaralanes were investigated theoretically for their possible bishomoaromatic character using correlated ab initio methods, when tetraazasemibullvalene and several phosphasemibullvalenes were found to have highly symmetric delocalized minima, possessing large negative nucleus independent chemical shift (NICS) values. 17 Following the principle of isolobal CH→BCO substitution, Schleyer and co-workers 7c showed that barrier to the degenerate Cope rearrangement was eliminated in the semibullvalenes having C2H, C4H, C6H, and C8H replaced by the BCO moieties (cf Scheme 1). In the case of barbaralanes, barbaralones and bullvalenes substituted in the 2,6-and 2,8,4,6-positions by BCO moieties, this barrier was substantially reduced.…”
Section: Introductionmentioning
confidence: 98%